Cocrystal engineering of molecular rearrangement: a "turn-on" approach for high-performance N-type organic semiconductors. Issue 25 (21st June 2021) - Wang, Wei; Luo, Lixing; Lin, Zongqiong; Mu, Zifeng; Ju, Zhengkun; Yang, Bo; Li, Yang; Lin, Menglu; Long, Guankui; Zhang, Jing; Zhao, Jianfeng; Huang, Wei
Abstract : From TCAF to binary α-phase cocrystals, an electron mobility of 0.06 cm 2 V −1 s −1 was found. Then by molecular rearrangement, β-cocrystals from heterogeneous nucleation growth showed a remarkable mobility up to 0.88 cm 2 V −1 s −1 . Abstract : Developing novel high-performance n-type semiconductors is of great importance for future organic electronics. Complicated synthesizing procedures of new electron deficient backbones or chemical modification to control the energy level and electron transport route limit their applications. Here, using PAH donor doping, we report that two polymorphs of TCAF based complexes act as efficient n-type semiconductors originating from inactive pristine material. These supramolecular structures possessed different donor–acceptor overlaps along the mixed π–π stacking direction with the same molar ratio of 1 : 1. Also the complete phase transition of the microcrystals on the substrate could happen under controllable solvent treatment. As a result, a large shift of electron mobility from 0.06 to 0.88 cm 2 V −1 s −1 was observed, due to the phase change. Quantum calculations confirmed that the polymorphic structure containing better overlaps allowed larger transfer integrals than that with distorted overlaps. The charge transport properties of the binary supramolecular system are highly correlated with the molecular orientations. This cocrystal engineering approach of phase control provides us new insight towards high performance n-type organic semiconductor exploration.